2017
DOI: 10.1093/aje/kwx295
|View full text |Cite|
|
Sign up to set email alerts
|

Examining the Association Between Apparent Temperature and Mental Health-Related Emergency Room Visits in California

Abstract: The association between ambient temperature and morbidity has been explored previously. However, the association between temperature and mental health-related outcomes, including violence and self-harm, remains relatively unexamined. For the period 2005-2013, we obtained daily counts of mental health-related emergency room visits involving injuries with an external cause for 16 California climate zones from the California Office of Statewide Health Planning and Development and combined them with data on mean a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
70
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(76 citation statements)
references
References 35 publications
4
70
0
2
Order By: Relevance
“…For example, temperature stress can influence psycho-physiological functions by directly affecting bio-chemicals levels, (e.g. altering the production of serotonin and dopamine) (120) or by disrupting the homeostasis of thermoregulation (121,122). Additionally, direct heat could result in sleep disturbance, exhaustion, and heat stress associated with suicide (56,123).…”
Section: Increase Of Average Land Surface Air Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…For example, temperature stress can influence psycho-physiological functions by directly affecting bio-chemicals levels, (e.g. altering the production of serotonin and dopamine) (120) or by disrupting the homeostasis of thermoregulation (121,122). Additionally, direct heat could result in sleep disturbance, exhaustion, and heat stress associated with suicide (56,123).…”
Section: Increase Of Average Land Surface Air Temperaturementioning
confidence: 99%
“…People are more affected by high temperature especially if they have schizophrenia, schizotypal disorders, and mood disorders (121). During the increase of temperature, there is a risk of mental states of aggression resulting in violence and self-harm, inflicted injury/homicide, and self-injury/suicide (122). Many studies found no significant associations with cold temperatures (51,120).…”
Section: Increase Of Average Land Surface Air Temperaturementioning
confidence: 99%
“…These impacts will be widespread, profound, and cumulative [3,6] and include elevated rates of anxiety and mood disorders, acute stress reactions and posttraumatic stress disorders, sleep disruption, suicide and suicidal ideation, substance use disorders, and a decreased sense of self and identity from loss of place and connection to the environment [1,2,[6][7][8][10][11][12][13][14][15][16][17][18][19][20]. Indeed, numerous studies have linked three specific forms of climate change to mental health impacts: (1) acute and extreme weather events (EWEs) and natural disasters, such as hurricanes [8,12], floods [13,14], wildfires [15], and heat waves lasting for days or weeks [16,17]; (2) sub-acute weather events lasting for months or years such as droughts [1,2,18,19] and longer-duration heat waves [1,2,20]; and (3) and a permanently altered and potentially uninhabitable physical environment that is either too dry or too wet, but ultimately too hot [1,2,4,5,7,9,10]. Each form of climate change can contribute to an increase in mental health problems that are directly linked to property damage, loss of income and employment opportunities and reduced economic productivity [1,…”
Section: Introductionmentioning
confidence: 99%
“…Several empirical studies and systematic reviews have documented the mental health impacts of global climate change [1][2][3][4][5][6][7][8][9][10][11]. These impacts will be widespread, profound, and cumulative [3,6] and include elevated rates of anxiety and mood disorders, acute stress reactions and post-traumatic stress disorders, sleep disruption, suicide and suicidal ideation, substance use disorders, and a decreased sense of self and identity from loss of place and connection to the environment [1,2,[6][7][8][10][11][12][13][14][15][16][17][18][19][20]. Indeed, numerous studies have linked three specific forms of climate change to mental health impacts: 1) extreme weather events (EWEs) and natural disasters lasting for days, such as hurricanes [8,12], floods [13,14], wildfires [15], and short-duration heat waves [16,17]; 2) sub-acute weather events lasting for months or years such as droughts [1,2,18,19] and long-duration heat waves [1,2,20]…”
Section: Introductionmentioning
confidence: 99%
“…These impacts will be widespread, profound, and cumulative [3,6] and include elevated rates of anxiety and mood disorders, acute stress reactions and post-traumatic stress disorders, sleep disruption, suicide and suicidal ideation, substance use disorders, and a decreased sense of self and identity from loss of place and connection to the environment [1,2,[6][7][8][10][11][12][13][14][15][16][17][18][19][20]. Indeed, numerous studies have linked three specific forms of climate change to mental health impacts: 1) extreme weather events (EWEs) and natural disasters lasting for days, such as hurricanes [8,12], floods [13,14], wildfires [15], and short-duration heat waves [16,17]; 2) sub-acute weather events lasting for months or years such as droughts [1,2,18,19] and long-duration heat waves [1,2,20]; and 3) environmental changes lasting to the end of this century and beyond such as higher temperatures, sea level rise, and a permanently altered and potentially uninhabitable physical environment [1,2,4,5,7,9,10]. Each form of climate change can result in varying degrees of economic losses associated with property damage, loss of income and employment opportunities and reduced economic productivity, especially in agriculture and fishe...…”
Section: Introductionmentioning
confidence: 99%